Factor Analysis of Machine Selection in Aquatec Smart Ship Design for Fish Farming Using The SPSS Method - Kusuma H, Nely Handayani; A.R., Anauta Lungiding; Irmiyana, Triyanti (Program Studi Budidaya Perairan Universitas Mataram, 2024)
In the manufacture of a floating building such as a ship requires a machine to be able to move. This study aims to analyze the factors that can influence the selection of engines that will have an impact on ship performance. The method was carried out through data collection which was distributed to 30 respondents. The analysis carried out includes validity and reliability. The results of the analysis were carried out in the form of an alpha value of more than 0.6 and a cronch's bach value of 0.705 so that the factors used were reliable. Where the factor that has the highest value is the calculation of resistance, namely 0.609. Next, the calculation of the resistance value is carried out to determine the engine power. The difference between the detainees through the help of the Maxsuf application and manual calculations is 0.91. So the results of calculating the power requirements of the Aquatec SMART ship design are 15 Hp.